Discovering miRNAs Associated With Multiple Sclerosis Based on Network Representation Learning and Deep Learning Methods - Sun, Xiaoping; Ren, Xingshuai; Zhang, Jie; Nie, Yunzhi; Hu, Shan; Yang, Xiao; Jiang, Shoufeng (Frontiers in Genetics, 2022)
Identifying biomarkers of Multiple Sclerosis is important for the diagnosis and treatment of Multiple Sclerosis. The existing study has shown that miRNA is one of the most important biomarkers for diseases. However, few existing methods are designed for predicting Multiple Sclerosis-related miRNAs. To fill this gap, we proposed a novel computation framework for predicting Multiple Sclerosis-associated miRNAs. The proposed framework uses a network representation model to learn the feature representation of miRNA and uses a deep learning-based model to predict the miRNAs associated with Multiple Sclerosis. The evaluation result shows that the proposed model can predict the miRNAs associated with Multiple Sclerosis precisely. In addition, the proposed model can outperform several existing methods in a large margin.